The influence of perceived behavioral control, attitude, and subjective norm on revisit intention of Komodo National Park in Labuan Bajo - Mayela Mboi; Siti Rahayu; Veny Megawati (Southeast Asian Journal of Service Management, 2025)
This study examines the influence of Perceived Behavioral Control, Attitude Toward the Behavior, and Subjective Norms on Revisit Intention to Komodo National Park in Labuan Bajo. Using non-probability sampling, data were collected from 175 visitors who had visited the park in the past 2–3 years. The analysis was conducted using SmartPLS. Results show that Subjective Norms, Perceived Behavioral Control, and Destination Image have a significant positive effect on Revisit Intention. In contrast, Attitude Toward the Behavior, Perceived Value, Perceived Risk, Perceived Service Quality, and Satisfaction do not significantly influence revisit intention. Additionally, Destination Image and Perceived Value significantly affect Satisfaction, while Perceived Service Quality does not. However, Perceived Service Quality positively influences Perceived Value. The study also finds that Satisfaction does not mediate the relationships between Perceived Service Quality, Destination Image, or Perceived Value and Revisit Intention. These findings highlight the stronger role of social and perceptual factors over individual attitudes in shaping revisit behavior.